Technological Innovations for Efficient Disaster Management and Healthcare Response: A Literature Review - Rika Yuliwulandari (Journal of Diverse Medical Research : Medicosphere, 2026)
Disasters pose significant challenges to global health systems. Traditional methods of disaster management often struggle with efficient resource allocation and communication, especially in densely populated metropolitan areas. Technological innovations, such as GIS, UAVs, and VR, offer new opportunities to address these challenges. This study assesses the combined impact of technologies on improving healthcare service delivery and resource management during disasters, particularly in urban environments. A systematic review was conducted using the PRISMA-ScR framework. The research identified and analyzed studies from databases such as PubMed, Scopus, Sage Journals, and Google Scholar, focusing on technology-based disaster management interventions between 2020 and 2024. The review included eight studies that demonstrated significant improvements in disaster preparedness and response through the use of technologies. These technologies enhanced real-time decision-making, reduced response times, and improved the allocation of healthcare resources. However, the studies also highlighted issues with scalability, interoperability, and the lack of real-world testing. The integration of technologies has the potential to revolutionize disaster management practices. Despite the advancements, further research is needed to address the scalability and operational challenges that limit the full deployment of these technologies in real-world disaster scenarios.